Operational Paradoxes: Vouchers and Catholic Elementary Schools - Cattaro, Gerald M. (Catholic Education: A Journal of Inquiry and Practice, 2003)
This article presents the results of a study of teacher education practices at 80 Catholic colleges and universities. The impetus for this work was the many Church documents in support of Catholic schools and the cooperative work of diocesan superintendents and educational leaders in the matter of teacher education. The goal of the study was to investigate questions fundamental to the role of Catholic higher education in the preparation of teachers: From where will the next generation of teachers to serve Catholic schools come? How does the preparation of teachers in Catholic institutions of higher education relate to the unique opportunities Catholic schools afford their communities? Do these programs serve Catholic schools? Given the dearth of research and professional literature specific to these questions, the study and data analysis were exploratory with the goal of identifying themes and issues for continued The U.S. Supreme Court has ruled in support of the constitutionality of the Cleveland voucher program. Will urban Catholic schools soon become filled with voucher students? Catholic school leaders have some important decisions to face, decisions which can be clarified by taking a historical view. research, dialogue, and professional action.